Built Environment Factors Influencing Walking to School Behaviors: A Comparison between a Small and Large US City - Kim, Hyung Jin; Heinrich, Katie M. (My University, 2016)
A growing body of evidence supports the association between the built environment and children walking to school (WTS), but few studies have compared WTS behaviors in cities of different sizes. This case-comparison study utilized WTS data from fourth graders in the small city of Manhattan, KS, USA (N = 171, from all eight schools) and data from fourth graders in the large city of Austin, TX, USA (N = 671 from 19 stratified-sampled schools). The same survey instrument was used in both locations. After controlling for socioeconomic and demographic variables, built environment, neighborhood, and attitudinal differences were demonstrated by the odds ratios for WTS in the small city vs. the large city. WTS in the small city was more likely to be associated with walking paths/trails and sidewalk landscape buffers en route to school despite lower perceived neighborhood social cohesion, school bus availability, and parental concerns about crime, compared to WTS in the large city. Also, the small city lacked key pedestrian infrastructure elements that were present in the large city. This study highlights important differences related to WTS behaviors and, thus, provides key insights for encouraging WTS in cities of different sizes.
Citation: Kim HJ and Heinrich KM (2016) Built Environment Factors Influencing Walking to School Behaviors: A Comparison between a Small and Large US City. Front. Public Health 4:77. doi: 10.3389/fpubh.2016.00077